The nature and consequences of physical development under overhead electricity power lines (EPLs) in Ibadan (2015)
"Infringement by the public through various physical development activities on lands under overhead electricity power lines (EPLs) has become a widespread practice in Nigerian cities in recent years. This study investigated the scenario along four feeders in Akinyele local government area (LGA) of Ibadan, Oyo State. Investigations revealed the causes of indiscriminate physical development and habitation of right-of-way of EPLs as: weak enforcement of development control regulations along transmission lines, lack of strong political will, shortage of manpower, inadequate operational funds, lack of cooperation between planning agency and electricity provider, and ignorance/lackadaisical attitude of the public to the effects of living under EPLs. Further analysis indicated significant difference in the distribution of ailments (such as high blood pressure, arthritis and skin cancer) between permanent and temporary structures under overhead EPLs in the study area (x2 = 9.19 (df = 4), P < 0.05). The paper advocates for a strong political will and strengthening of local planning authorities for effective control of physical developments among other mitigation measures. "